Дослідження функціонального стану нервової системи військо¬вослужбовців, які мали контузію шляхом використання скринінг-тестів - Artur Oderov; Serhii Romanchuk; Oleh Nebozhuk; Mariana Ripak; Oksana Matveiko; Viktor Lashta; Volodymyr Klymovych; Oleksandr Тymochko (Lesya Ukrainka Volyn National University, 2022)
Analysis of servicemen participation in hostilities on the territory of the state has led to a significant increase in the number of personnel who have combat wounds, mutilations or injuries. Almost all participants in hostilities have health impairments, namely PCS, the prevalence of which is more than 70 % of the total number of injuries. This contingent of servicemen is important for the Ukrainian army, as their combat experience is a basis for the development and improvement of training of military specialists` training. However, their state of health can be an obstacle to the successful performance of their functional duties. The Purpose of the Study - to comprehensively investigate the functional state of the nervous system of servicemen who had PCS, using a battery of tests aimed at studying the psycho-emotional state. Research Stuff and Methods - 36 servicemen (average age 32,22±1,26 years) who had a history of concussion took part in the study. A set of tests included: tapping test, the Romberg test, finger-nose test, "Walking in a straight line with open and closed eyes" test, and the Yarotsky`s test. Findings. The tests used meet the basic requirements for screening, it means, they are simple, visual, economically feasible and allow obtaining sufficiently informative information about the health state of the participants. The absence of deep lesions of the nervous system was confirmed, that is, the testing proves the conclusions made regarding the pre-nozological nature of health disorders again.